2019
DOI: 10.1075/sar.17012.bej
|View full text |Cite
|
Sign up to set email alerts
|

Adult second language learners’ social network development and perceived fluency gain in an intensive English program abroad

Abstract: This study investigated the social networks developed by language learners during 14 weeks of an intensive English as a second language (ESL) program using the Study Abroad Social Interaction Questionnaire (Dewey, Bown, Baker, Martinsen, Gold, & Eggett, 2014;Dewey, Bown, & Eggett, 2012). It also utilized native speaker judgments to evaluate ESL fluency development. Results showed that participants were successful in developing complex social networks, that their oral fluency increased significantly, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…With only five consistent anchors -her host parents, her partner, and her two classmates -Nancy's small social network was defined by quality over quantity of social engagement, confirming previous findings on the benefits of quality social contacts during SA (Alonso-Marks & Sánchez Hernández, 2020;Arvidsson, 2019;Baker-Smemoe et al, 2014;Baten, 2020;Bejarano et al, 2019;Gaugler & Matheus, 2019;McManus, 2019;Mitchell et al, 2017;Tullock & Ortega, 2017).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With only five consistent anchors -her host parents, her partner, and her two classmates -Nancy's small social network was defined by quality over quantity of social engagement, confirming previous findings on the benefits of quality social contacts during SA (Alonso-Marks & Sánchez Hernández, 2020;Arvidsson, 2019;Baker-Smemoe et al, 2014;Baten, 2020;Bejarano et al, 2019;Gaugler & Matheus, 2019;McManus, 2019;Mitchell et al, 2017;Tullock & Ortega, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…investigating "what social networks and practices learners are embedded in and which languages mediate their relationships and interactions" to determine how growth is supported (p. 14). Studies have concurred that quality of social interactions matters more than quantity in predicting language gains (Arvidsson, 2019;Baker-Smemoe et al, 2014;Baten, 2020;Bejarano et al, 2019;Gaugler & Matheus, 2019;McManus, 2019;Mitchell et al, 2017;Tullock & Ortega, 2017) and intercultural growth (Alonso-Marks & Sánchez Hernández, 2020;Baker-Smemoe et al, 2014;Mitchell et al, 2017). Considerable imbalance between contacts with locals (rare) and co-nationals (unavoidable) has also been found (Compiegne, 2021;Mas-Alcolea & Torres-Purroy, 2022;Seibert Hanson & Dracos, 2019), attributable to program structure, with SA students often taking classes among themselves, forming "self-contained enclaves" (Mas-Alcolea & Torres-Purroy, 2022, p. 13).…”
Section: Social Engagementmentioning
confidence: 99%
“…Baten (2020) concludes that deep relationships with L2 speakers are key to language gains during the SA experience. Bejarano, Dewey, Baker-Smemoe, Henrichsen, and Hall (2019) also found that L2 English learners in an intensive English SA experience in the US with larger L2 social network groups had more significant gains in L2 oral fluency than those with smaller L2 social networks. This was likely due to the richer and more varied L2 use experience a larger L2 social network affords.…”
Section: Language Exposure/experiencementioning
confidence: 73%
“…This has led to more recent research examining social resources as a window to understand the nature of language contact during SA. The consensus seems to be that the higher the level of dispersion (i.e., number of social groups), density (i.e., average size of social groups), and intensity (i.e., closeness of the relationship with individuals in social groups) in a learner's social network, the greater the linguistic gain the learner tended to experience (Baker–Smemoe et al., 2014; Bejarano et al., 2019; Dewey et al., 2014).…”
Section: Transdisciplinary Framework and Sa Researchmentioning
confidence: 99%